1995
DOI: 10.3109/00365599509180578
|View full text |Cite
|
Sign up to set email alerts
|

Clinical And Urodynamic Effects of Propiverine in Patients Suffering from Urgency and Urge Incontinence

Abstract: The efficacy and tolerability of propiverine hydrochloride (15, off 45, 60 mg/d) were evaluated in the treatment of 185 patients suffering from urgency/urge incontinence in an open, randomized, multicentre parallel-group trial lasting 21 days. The effects on bladder volume and pressure were assessed on the basis of urodynamics and micturition frequency. Subjective adverse reactions were recorded. The bladder capacity and compliance increased and bladder pressure decreased in a dose dependent manner following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 6 publications
1
18
0
2
Order By: Relevance
“…In agreement with previous studies [20, 21, 22, 23, 24], propiverine was very well tolerated in the elderly patient population. The incidence of adverse events was very low, reflecting the well–known experience that effective treatment correlates with minor complaints of undesirable effects [21].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In agreement with previous studies [20, 21, 22, 23, 24], propiverine was very well tolerated in the elderly patient population. The incidence of adverse events was very low, reflecting the well–known experience that effective treatment correlates with minor complaints of undesirable effects [21].…”
Section: Discussionsupporting
confidence: 81%
“…Numerous previous studies have demonstrated the efficacy of propiverine in the treatment of urgency and urge incontinence [20, 21, 22, 23, 24]. Comparable improvements have been documented by applying invasive cystometric and non– invasive parameters of micturition diaries.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The ecacy of propiverine (15,30,45, 60 mg/d) was evaluated in 185 patients suering from urgency (n 105) and urge incontinence (n 80) in an open, randomised, multicentre parallel group trial for 21 days [40]. Of these patients, 80% suered from detrusor instability veri®ed by urodynamics.…”
Section: Dosage-optimising Studiesmentioning
confidence: 99%
“…Open studies in patients with detrusor overactivity have demonstrated a beneficial effect [46], and in a double-blind placebo-controlled trial of its use in detrusor hyperreflexia it has been shown to significantly increase bladder capacity and compliance compared to placebo. Dry mouth was experienced by 37% in the treatment group, as opposed to 8% in the placebo group, with dropout rates being 7% and 4.5%, respectively [47].…”
Section: Propiverinementioning
confidence: 99%